دعوت وتفہیم دین : شرعی حیثیت ،ارکان،شرائط اور طریق کار (Al-Qamar, 2020)
Islam is a religion of comprehensive and inclusive teachings and is a source of guidance and enlightenment for humans till the day of judgement. Allah sent prophets to spread the message of Islam among human race. Hazrat Adam (A.S) commended the preaching of Dīn, the latter prophets and messengers continued it and the Holy Prophet Muhammad (PBUH) marked the completion of this message of Dīn. From the period of the Holy Prophet Muhammad (PBUH) thus far, the process of the preaching of Dīn never discontinued. However, the preachers, adopted various methodologies to spread the message. Some literati broadened the message though pen and others through speeches. Some preached Islam though their doings and actions and others adopted mysticism to spread the message of Dīn. The following research paper discusses about the types of Islamic preaching, fundamentals, conditions, methodologies and understanding in current era.
Keywords: Dīn; Understanding; Conditions; Methodology